Crystallization and preliminary X-ray characterization of the eukaryotic replication terminator Reb1-Ter DNA complex - Jaiswal, Rahul (2015)
The Reb1 protein from Schizosaccharomyces pombe is a member of a family of proteins that control programmed replication termination and/or transcription termination in eukaryotic cells. These events occur at naturally occurring replication fork barriers (RFBs), where Reb1 binds to termination (Ter) DNA sites and coordinates the polar arrest of replication forks and transcription approaching in opposite directions. The Reb1 DNA-binding and replication-termination domain was expressed in Escherichia coli, purified and crystallized in complex with a 26-mer DNA Ter site. Batch crystallization under oil was required to produce crystals of good quality for data collection. Crystals grew in space group P21, with unit-cell parameters a = 68.9, b = 162.9, c = 71.1 Å, β = 94.7°. The crystals diffracted to a resolution of 3.0 Å. The crystals were mosaic and required two or three cycles of annealing. This study is the first to yield structural information about this important family of proteins and will provide insights into the mechanism of replication and transcription termination.